The autographs of Salvator Rosa at the Ambrosiana Library: first results (Prassi Ecdotiche della Modernità Letteraria, 2020)
This paper focuses on the autographs of Salvator Rosa’s Satires, conserved in the Veneranda Biblioteca Ambrosiana (S.P.63) and never examined; in particular, it offers the first results of the investigation on the autographs of satires La Musica, La Poesia, La Pittura. The first attempt to establish the critical text of the seven satires, composed between 1641 and 1663 (and printed in about 1694), dates back to 1892, for the care of Giovanni Alfredo Cesareo; but, by his own admission, the recensio of manuscripts is incomplete. His edition is still being used. The new textual arrangement will take into account also the autographs conserved in the Biblioteca Ambrosiana.
Keywords: Salvator Rosa; Biblioteca Ambrosiana; satires; autographs; philology